Exploring the potential for touchless interaction in image-guided interventional radiology - Johnson, Rose; O'Hara, Kenton; Sellen, Abigail; Cousins, Claire; Criminisi, Antonio (Proceedings of CHI 2011, 2011)
The growth of image-guided procedures in surgical settings has led to an increased need to interact with digital images under sterile conditions. Traditional touch-based interaction techniques present challenges for managing asepsis in these environments leading to suggestions that new touchless interaction techniques may provide a compelling set of alternatives. In this paper we explore the potential for touchless interaction in image-guided Interventional Radiology (IR) through an ethnographic study. The findings highlight how the distribution of labour and spatial practices of this work are organised with respect to concerns about asepsis and radiation exposure, the physical and cognitive demands of artefact manipulation, patient management, and the construction of “professional vision”. We discuss the implications of these key features of the work for touchless interaction technologies within IR and suggest that such issues will be of central importance in considering new input techniques in other medical settings.